تنوع براغماتية الخطاب الإشهاري وحدود الانفتاح الدلالي "قناة الفجر الجزائرية أنموذجا" - حفري, فطيمة الزهرة; حنكة, العيد (جامعة الوادي university of eloued, 2023)
لا جرم أن الخطاب الإشهاري اليوم يبعث على إلطاف النظر، وتدقيق التأمل في مفهوم البراغماتية الإشهارية، والتي اكتسحت نطاقا واسعا في شتى القنوات. وكان حري بنا أن نقف أمام أسئلة تفرض نفسها مؤداها: البحث عن الطاقة الدلالية للإشهار؟ وتحديد المعطى النفعي في ذلك؟. تتجاوز عديد القنوات الجزائرية وعلى رأسها "قناة الفجر" في تقديمها للبرامج إلى الفواصل الإشهارية، وكثيرا ما يتموقع فضاء الإشهار تموقعا تتحول من خلاله عملية المشاهدة من تتبع إلى بحث قوامه اختصار الرحلة الشاقة التي يروم فيها المشاهد أهدافا جمة أهمها: التطبيب، الخدمات، العقار، الأسفار والرحلات...الخ. في خاتمة المطاف، نؤكد على براغماتية الإشهار من خلال حسية المعنى المدرك الذي يتفانى في تصويغه جهات تستثمر الحواس، وقدرتها على الربط بين ما هو ذهني وما هو واقعي. Abstract: There is no doubt that the publicity discourse today is a matter of lightening consideration and scrutiny of the concept of advertising pragmatism, which has swept a wide range in various channels. We should have faced self-imposed questions: the search for the semantic power of advertising? And determine the utilitarian givens in that? Many Algerian channels, on top of which are "Al-Fajr Channel", go beyond their presentation of programs to advertising breaks, and the advertising space is often positioned as a location through which the viewing process turns from tracking to research based on shortening the arduous journey in which the viewer aims for many goals, the most important of which are: Medicine, services, real estate, travel and excursions... etc. In conclusion, we emphasize the pragmatism of publicity through the sensuality of the perceived meaning, which is devoted to justifying it by parties that invest the senses, and their ability to connect between what is mental and what is realistic
مقال
Keywords: البراغماتية –التفاعل- الأثر- الانفتاح – الكينونة; pragmatism - interaction - impact - openness - being.